21st Panhellenic Congress of Thoracic Disease 1-4 November 2012, Thessaloniki, Greece - Zarogoulidis, Paul; Kosmatopoulos, Konstantinos; Morice, Alyn; Bouros, Demosthenes; Freitag, Lutz; Casalini, Angelo G.; Froudarakis, Marios; Panadero, Francisco Rodriguez; Manika, Katerina; Galanis, Nikolaos; Leonidas, Sakkas; Papagiannis, Antonis; et al. (Journal of Thoracic Disease; Vol 4, Supplement 1 (November 11, 2012): Journal of Thoracic Disease, 2012)
The annual Panhellenic Congress of Thoracic Disease has been established as the biggest scientific event held in Greece for pneumonologists, thoracic surgeons and paediatric pneumonologists. Since its establishment in 1984, it has provided a unique forum for presentation of scientific research, an opportunity to review the latest knowledge on the whole spectrum of lung diseases, and a venue for informal sharing of information and research experience with Greek and foreign expert colleagues.